Enhancement of Emergence and Vigour of Bottle gourd Seed under Subtropical Conditions - RAJINDER SINGH (Seed Research, 2026)
The present investigation was carried at Vegetable Research Farm of Department of Vegetable Science, Punjab Agricultural University, Ludhiana. The experiment was laid in completely randomized design with nine priming treatments along with control. The seeds of bottle gourd were treated with PEG 6000 @ 0.5 Mpa and 1.5 Mpa, disodium hydrogen phosphate @ 10 M and 10³M, KH2PO4 @ 10¹ and M 103 M, GA, @ 100 ppm and 500 ppm, hydration for 24 hours and 48 hours. Seeds were sown in polythene bags during second week of February 2011, 2012 and 2013. The results revealed that pre sowing treatment with KH2PO4 @ 10 M resulted in maximum field emergence (%), speed of emergence, seedling dry weight and vigour index II whereas seedling length and vigour index-I better in treatment GA3 @ 100 ppm and 500 ppm.